2015
DOI: 10.1002/adem.201500179
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Al8Co17Cr17Cu8Fe17Ni33, Al23Co15Cr23Cu8Fe15Ni15, and Al17Co17Cr17Cu17Fe17Ni17 Compositionally Complex Alloys (High‐Entropy Alloys) at Elevated Temperatures in Air

Abstract: Oxidation behavior of the compositionally complex alloys (high-entropy alloys) Al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 21 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…They have also been considered for high-temperature applications due to their supposed sluggish diffusion kinetics and softening resistance at elevated temperatures (Ref 6,7). This has led to hightemperature oxidation studies of several HEA systems, such as CoCrFeMnNi, AlCoCrFeNi and AlCoCrCuFeNi (Ref [8][9][10][11][12][13][14]. These investigations have also been carried out on high-entropy materials consisting of elements that constitute refractory alloys, e.g., Ti, Ta, Mo, Nb, Hf, Cr and Zr (Ref [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…They have also been considered for high-temperature applications due to their supposed sluggish diffusion kinetics and softening resistance at elevated temperatures (Ref 6,7). This has led to hightemperature oxidation studies of several HEA systems, such as CoCrFeMnNi, AlCoCrFeNi and AlCoCrCuFeNi (Ref [8][9][10][11][12][13][14]. These investigations have also been carried out on high-entropy materials consisting of elements that constitute refractory alloys, e.g., Ti, Ta, Mo, Nb, Hf, Cr and Zr (Ref [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These studies include both transition metal based [6,7,[14][15][16][17][18][19][20][21][22][23][24][25] and refractory metal based [26][27][28][29] HEA systems. In general, it was reported that elements that commonly oxidize in less-complex, conventional alloy systems (i.e., Ni, Mn, Cr, Al, Ti) also tend to preferentially oxidize in compositionally complex alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it was reported that elements that commonly oxidize in less-complex, conventional alloy systems (i.e., Ni, Mn, Cr, Al, Ti) also tend to preferentially oxidize in compositionally complex alloys. For example, Daoud et al [23] Ni 17 HEAs at 800 • C and 1000 • C in air. At 800 • C, the low Al content alloy formed a combination of NiO, Fe-oxide, Cr 2 O 3 , and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[33] Due to the ambiguity over the role of entropy in solid solution formation, a few research groups have suggested referring the HEAs as multi-principal element alloys (MPEAs), baseless alloys, concentrated solid solution alloys (CSAs), and compositionally complex alloys (CCAs). [6,30,[34][35][36][37][38][39][40] Regardless of multiple phases or compound formation, it is worth mentioning that the significant concentration of various elements is present in the secondary phases/compounds. Besides, HEAs are established to have four inherent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…They observed the better compressive properties when the sample was annealed at 1000 C for 24 h. They concluded that the high ultimate tensile strength after annealing was mainly due to the disordering of FCC phase which can sustain more deformation than the ordered structure. Xian et al [220] developed a new V 35 Ti 33 Fe 15 Cr 10 Zr 5 HEA with single BCC phase for fusion reactors in the temperature range of 25-900 C. The yield strength of the alloy increased with increasing temperature below 500…”
mentioning
confidence: 99%